Price Perception, Product Variety, Service Quality, and Promotion: Their Influence on Consumer Purchase Decisions at Superindo Boyolali - Maharani, Putri Septia; Wiyadi, Wiyadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the influence of price perception, product variety, service quality, and promotion on consumer purchasing decisions at Superindo Boyolali. Data were collected through questionnaires distributed to randomly selected consumer respondents. Multiple linear regression analysis was conducted to test the research hypotheses. The results indicate that price perception has a positive and significant influence on consumer purchasing decisions at Superindo Boyolali (β = 0.327, p < 0.05). On the other hand, product variety does not have a significant influence on purchasing decisions (β = 0.092, p > 0.05). Service quality also has a positive and significant influence on purchasing decisions (β = 0.421, p < 0.05). Meanwhile, promotion does not have a significant influence on purchasing decisions (β = 0.055, p > 0.05). In conclusion, price perception and service quality have a significant influence on consumer purchasing decisions at Superindo Boyolali. However, product variety and promotion do not have a significant influence. Therefore, it is recommended that the management of Superindo Boyolali pay more attention to the aspects of price perception and service quality in efforts to improve consumer purchase decisions.